Phase 1/2 Trial of Durvalumab and Lenalidomide in Patients with Cutaneous T Cell Lymphoma (CTCL): Preliminary Results of Phase I Results and Correlative Studies - Querfeld, Christiane; Zain, Jasmine M.; Wakefield, Devin L.; Jovanovic-Talisman, Tijana; Kil, Sung Hee; Estephan, Renee; Sanchez, James; Palmer, Joycelynne; Rosen, Steven T (Blood, 2018)
Background: In CTCL, intratumoral T cells are functionally exhausted and are characterized by the expression of immune inhibitory molecules such as PD1 and PD-L1 (Cancer Immunol Res 6; 2018). These findings justify the evaluation of immune checkpoint inhibition to reverse T cell exhaustion in CTCL. To this end, we initiated a phase 1/2 clinical trial of lenalidomide and durvalumab to determine the safety and efficacy of this regimen. Durvalumab is a human monoclonal antibody with high affinity and selectivity for PD-L1, with mechanisms of action that target the exhausted T cells and distinct cells within their environment. Lenalidomide, an oral immunomodulatory drug and analog of thalidomide, has previously shown activity in CTCL (Blood 123; 2014). Durvalumab may restore an anti-tumor immune response, and the combination of durvalumab and lenalidomide may enhance immune checkpoint blockade-induced immune responses. Methods: A Phase 1 portion is ongoing to characterize the safety and tolerability of durvalumab and lenalidomide combination. Patients (pts) are enrolled in sequential cohorts to receive durvalumab (fixed dose at 1500 mg) and dose escalation of lenalidomide (cohort 1 = 10 mg; cohort 2 = 15 mg; subsequent planned dose increments of 5 mg) to evaluate safety, efficacy and antitumor activity. Serial skin and blood samples were collected to assess the impact on the tumor micro-environment. We examined the correlation between clinical response and resistance and the following biological factors: PD1 clustering at the single molecule level using super-resolution microscopy, and expression of PD-L1 and ICOS at the tissue level by means of multiplex immunohistochemistry on pre-treatment primary cells (migrated from skin explants), and skin tissue (formalin-fixed and paraffin-embedded) from clinical trial subjects. Results: Six patients (5 males/1female, age 32-57 years) with refractory/advanced CTCL (mycosis fungoides/Sezary syndrome subtype), clinical stage IB (1), IIA (1), IIB (3), IIIA (1) have been enrolled as of July 2018. Duration time on treatment was 4 to 13+ months. Four patients showed improvement of skin disease with 2 patients achieved partial response with > 90% improvement of skin disease by mSWAT. Two patients developed progressive disease. No serious adverse events (AEs) were observed. The most frequently reported AEs were fatigue (n=6), skin pain (n=4), anemia (n=3) chills (n=4), and decreased appetite (n=3). All treatment-related AEs were Grade 1 or 2 in severity. One grade 3 fatigue occurred in one patient. No dose limiting toxicity has been observed to date. Using multispectral microscopy, we analyzed expression panels of several checkpoints: PD1, PD-L1, and ICOS on lesional skin biopsies at baseline. Strong PD-L1 and ICOS expression is observed from non-responders. Detectable levels of PD-L1, but low levels of ICOS is observed in responding patients. Quantitative super-resolution microscopy detected nanoscale clusters of PD1 in T cells from responders and no PD1 clustering was observed in T cells from non-responders. Conclusions: Durvalumab/lenalidomide has significant clinical activity in patients with refractory/advanced CTCL, which will be formally evaluated in the Phase 2 portion of this trial. Responses were durable and ongoing, and treatment was well tolerated with a low toxicity profile. Dose escalation is planned up to lenalidomide 20 mg daily. Our preliminary results from patients on trial demonstrated that immune signatures on skin biopsies at baseline may be predictive of response to checkpoint blockade and yield insights into mechanisms of therapeutic resistance. Querfeld:Acelion: Membership on an entity's Board of Directors or advisory committees; Kyowa: Membership on an entity's Board of Directors or advisory committees; Bioniz: Membership on an entity's Board of Directors or advisory committees; Medivir: Membership on an entity's Board of Directors or advisory committees; Trillium Therapeutics: Membership on an entity's Board of Directors or advisory committees.